Immunohistochemical parameters in prognosis of the locally advanced cervical cancer - O. N. Churuksaeva; L. A. Kolomiyets; O. V. Savenkova; V. V. Nedosekov (Опухоли женской репродуктивной системы)
This review estimates immunohistochemical parameters reflecting apoptotic, proliferative activities, participating in angiogenesis and defining biological behavior of the tumor because treatment outcomes of locally advanced cervical cancer remain poor. Disease recurrences occur within the first two years after treatment in half of the patients. At the same time, many issues concerning the role of various indices of tumor growth as prognostic factors are controversial. Therefore, the study of histological patterns and molecular-biological characteristics of the tumor and their influence on short- and long-term treatment results are of great importance. The study of biological markers for locally advanced cervical cancer will allow physicians to understand tumor status, to predict the disease and to individualize treatment plan.